Notion and Meaning of Evidence Verification in Criminal Procedure - KOSTENKO, Roman V.; RUDIN, Artem (Journal of Advanced Research in Law and Economics, 2018)
This article deals with the main topical issues of the notion and meaning of evidence verification in criminal procedure. Notwithstanding many scientific studies of various years, there are still many outstanding issues and conflicting opinions concerning the purposes, methods, subjects and procedural order of evidence verification. In law, the regulation of some procedural aspects related to verification is obviously insufficient. After all, this situation negatively influences the quality of preliminary investigation and a judicial decision passed. Meanwhile, the development of a unified scientific approach and clear legal regulation could facilitate the solution of important practical aspects, namely, the proof of fault and the quality of punishment imposed. In view of the foregoing, the authors of this article aim at analyzing all available information about evidence verification as an element of preliminary investigation to develop theoretical provisions that provide answers to outstanding issues as well as to improve regulations of Russian criminal procedure. This analysis comprises opinions of criminal procedure researchers, including foreign ones, and regulations of Russian criminal procedure law. The evidence verification and its purposes are considered by the authors in the context of the proper understanding of the very process of evidence in criminal cases. The authors represent the structural elements of the evidence process in close interrelation. Basing on the analysis of certain provisions of the Criminal Procedure Code of the Russian Federation, the authors conclude that the evidence verification is aimed at clarifying their reliability, relevance and admissibility. The attitude of this article’s authors may become a matter of scholarly discussion in future, and theoretical provisions developed by the authors may be used in learning aids and practical manuals for those who carry out preliminary investigation, and proposals for improving rules of procedure may be considered for supplementing procedural law.